Network governance and the Urban Nexus of water, energy, and food: lessons from Amsterdam - Moises Covarrubias (Energy, Sustainability and Society, 2019)
Abstract Background Silo-thinking stands for one-dimensional and sectorial policy and decision-making in which natural resources managers do not reflect on interrelations between different sectors involved in the management of resources. Nexus-thinking stands out as a way of breaking down silos by identifying and understanding the interconnectedness of multiple resource flows within a determined spatial and temporal context, as in our case study of the flows of water, energy, and food (WEF) in the city of Amsterdam. To further the conceptualization and analysis of the Urban Nexus, this research introduces the theoretical perspective of networks and flows as developed in sociology by Manuel Castells. It offers a set of concepts to analyze how networks of WEF integrate or fail to do so, what the main actors are in connecting and configuring WEF networks, and how they interact. Method We analyze how the structure and function and power dynamics of networks play out in the WEF Nexus. We use the city of Amsterdam as a case study because this city offers examples of how networks of provisioning are being integrated in innovate ways. Results Amsterdam managed to realize a certain level of nexus dynamics in its existing WEF networks. The nexus in Amsterdam so far has materialized at a start-up or experimental level which proved feasible for trying out innovative approaches towards sustainability in interconnected flows of WEF. Conclusions However, the studied projects still have to find their way in terms of becoming more prevailing modes for organizing water, energy, and food provisioning in the future.